Multi-objective optimization of hydrant flushing in a water distribution system using a fast hybrid technique. (15th May 2023) - Shoorangiz, Mostafa; Nikoo, Mohammad Reza; Šimůnek, Jirka; Gandomi, Amir H.; Adamowski, Jan Franklin; Al-Wardy, Malik
Abstract: As a critical element in preserving the health of urban populations, water distribution systems (WDSs) must be ready to implement emergency plans when catastrophic events such as contamination events occur. A risk-based simulation-optimization framework (EPANET–NSGA-III) combined with a decision support model (GMCR) is proposed in this study to determine optimal locations for contaminant flushing hydrants under an array of potentially hazardous scenarios. Risk-based analysis using Conditional Value-at-Risk (CVaR)-based objectives can address uncertainties regarding the mode of WDS contamination, thereby providing a robust plan to minimize the associated risks at a 95% confidence level. Conflict modeling by GMCR achieved an optimal compromise solution within the Pareto front by identifying a final stable consensus among the decision-makers involved. A novel hybrid contamination event grouping-parallel water quality simulation technique was incorporated into the integrated model to reduce model runtime, the main deterrent in optimization-based methods. The nearly 80% reduction in model runtime made the proposed model a viable solution for online simulation-optimization problems. The framework's capacity to address real-world problems was evaluated for the WDS operating in Lamerd, a city in Fars Province, Iran. Results showed that the proposed framework was capable of highlighting a single flushing strategy, which not only optimally reduced risks associated with contamination events, but provided acceptable coverage against such threats, flushing 35–61.3% of input contamination mass on average, and reducing average time-to-return to normal conditions by 14.4–60.2%, while employing less than half of the initial potential hydrants. Graphical abstract: Image 1 Highlights: Hydrant flushing is a practical way to deal with incidents of contamination. Critical injection nodes, times, and durations are considered injection parameters. Risk-based analysis using CVaR can address uncertainties about the contamination mode. Hybrid event grouping-parallel water quality simulation reduces runtime dramatically. GMCR with a comprehensive viewpoint shows promise in decision-making.